COVID-19 and athletes: Endurance sport and activity resilience study—CAESAR study - Śliż, Daniel; Wiecha, Szczepan; Ulaszewska, Katarzyna; Gąsior, Jakub S.; Lewandowski, Marcin; Kasiak, Przemysław Seweryn; Mamcarz, Artur (Frontiers in Physiology, 2022)
Background The COVID-19 pandemic and imposed restrictions influenced athletic societies, although current knowledge about mild COVID-19 consequences on cardiopulmonary and physiologic parameters remains inconclusive. This study aimed to assess the impact of mild COVID-19 inflection on cardiopulmonary exercise test (CPET) performance among endurance athletes (EA) with varied fitness level. Materials and Methods 49 EA (nmale=43, nfemale=6, mean age= 39.94±7.80 yr., height= 178.45 cm, weight= 76.62 kg; BMI = 24.03 kg·m−2) underwent double treadmill or cycle ergometer CPET and body analysis (BA) pre- and post-mild COVID-19 infection. Mild infection was defined as: (1) without hospitalization and (2) without prolonged health complications lasting for >14 days. Speed, power, heart rate (HR), oxygen uptake (VO2), pulmonary ventilation, blood lactate concentration (at the anaerobic threshold (AT)), respiratory compensation point (RCP), and maximum exertion were measured before and after COVID-19 infection. Pearson’s and Spearman’s r correlation coefficients and Student t-test were applied to assess relationship between physiologic or exercise variables and time. Results The anthropometric measurements did not differ significantly before and after COVID-19. There was a significant reduction in VO2 at the AT and RCP (both p<0.001). Pre-COVID-19 VO2 was 34.97±6.43 ml·kg·min-1, 43.88±7.31 ml·kg·min-1 and 47.81±7.81 ml·kg·min-1 respectively for AT, RCP and maximal and post-COVID-19 VO2 was 32.35±5.93 ml·kg·min-1, 40.49±6.63 ml·kg·min-1 and 44.97±7.00 ml·kg·min-1 respectively for AT, RCP and maximal. Differences of HR at AT (p<0.001) and RCP (p<0.001) was observed. The HR before infection was 145.08±10.82 bpm for AT and 168.78±9.01 bpm for RCP and HR after infection was 141.12±9.99 bpm for AT and 165.14±9.74 bpm for RCP. Time-adjusted measures showed significance for body fat (r=0.46, p<0.001), fat mass (r=0.33, p=0.020), cycling power at the AT (r=-0.29, p=0.045), and HR at RCP (r=-0.30, p=0.036). Conclusions A mild COVID-19 infection resulted in a decrease in EA's CPET performance. The most significant changes were observed for VO2 and HR. Medical Professionals and Training Specialists should be aware of the consequences of a mild COVID-19 infection in order to recommend optimal therapeutic methods and properly adjust the intensity of training.